NEW EXPLORATION OF TALENT INCENTIVES IN CATERING ENTERPRISES UNDER STRATEGIC MANAGEMENT PRACTICE: CASE OF GUANGZHOU RESTAURANT - MAZORENKO, Oksana; BOBLOVSKYI, Oleksandr; WU, Zhou (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article deeply analyzes how catering enterprises, relying on strategic management practices, carefully carve out the talent incentive mechanism of catering enterprises, thereby revitalizing the enterprise. We not only explore the positive role of various theoretical frameworks and management strategies such as scientific management principles, economic incentive mechanisms, and team dynamics principles in talent incentives, but also through a meticulous analysis of Guangzhou Restaurant, reveal the core driving force of leadership in the incentive chain, the indispensability of teamwork in creating an atmosphere, the direct improvement of talent satisfaction by rational resource allocation, and the solid backing of risk management in ensuring the sense of security of talents. Faced with the various challenges of personnel incentives in catering enterprises, we analyze them individually and propose coping strategies. At the same time, this article emphasizes the critical role of personalized salary plans, diversified incentives, and continuous communication in stimulating talent potential and innovative vitality. Suggested recommendations are formed for the Guangzhou Restaurant. Guangzhou Restaurant cleverly integrates material incentives with non-material incentives, greatly enhancing talents' loyalty and work enthusiasm. This article focuses on the outstanding contribution of Guangzhou Restaurant's strategic management in optimizing talent incentives and improving team performance. It provides valuable references and inspiration for other catering companies in talent management and incentives, helping them to stand out in the fierce market competition and move forward steadily.
Keywords: Guangzhou Restaurant; strategic management; catering enterprise; personnel motivation; talent incentive; optimization and improvement